2020
DOI: 10.12998/wjcc.v8.i21.5371
|View full text |Cite
|
Sign up to set email alerts
|

Seven-year follow-up of the nonsurgical expansion of maxillary and mandibular arches in a young adult: A case report

Abstract: BACKGROUND Palatal expansion treatment has been used to expand the constricted maxillary arch and has become a routine procedure in orthodontic practice over the past decades. However, the long-term stability of expansion in the permanent dentition without a surgical approach is uncertain. CASE SUMMARY We present the case of a 15-year-old boy with Class II malocclusion and constricted arches. The patient was treated with rapid palatal expansion (RPE) followed by a fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Research conducted using acrylic splint RPE showed a wider difference than Hyrax-Haas [13]. Several reports have shown that the Haas type of palatal expander can produce better therapeutic results due to the acrylic pads propped up on the palate [14]. The use of RPE for posterior cross bite correction can use quadhelix type more efficiently than the use of removable appliances, both approaches with quad helix and removable RPE produce changes in teeth compared to changes in bone [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted using acrylic splint RPE showed a wider difference than Hyrax-Haas [13]. Several reports have shown that the Haas type of palatal expander can produce better therapeutic results due to the acrylic pads propped up on the palate [14]. The use of RPE for posterior cross bite correction can use quadhelix type more efficiently than the use of removable appliances, both approaches with quad helix and removable RPE produce changes in teeth compared to changes in bone [14].…”
Section: Resultsmentioning
confidence: 99%
“…Spontaneous correction of patients with a propensity for class II malocclusion cannot be expected during the period of active expansion but rather during the period of retention patients treated with RPE equipment after long-term evaluation. A number of investigators have investigated the stability of the RPE, and factors such as patient age, length of retention period, rate of expansion, device design, and biologic response of the maxillary sutures suggest that expansion of the maxillary and mandibular arches followed by fixed orthodontic appliances causes an increase in width 5 to 7 mm arch in young adult patients [14].…”
Section: Discussionmentioning
confidence: 99%
“…RPE has been used for over a century as a treatment for maxillary constriction [ 7 ]. In this case, a Hyrax expander was initially used to address the patient’s maxillary transverse deficiency and teeth crowding without the need for extraction.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of wear should be as long as possible, as wearing the device more frequently leads to better and faster results. The minimum recommended period for wearing headgear is 14 to 16 hours per day [ 6 - 7 ]. When the maxilla moves, the force vector should pass through the center of resistance of the maxilla to achieve bodily movement.…”
Section: Introductionmentioning
confidence: 99%